Male perceptions of post-abortion care in Karachi, Pakistan. (2nd December 2022) - Khan, Inayatullah; Ali, Tazeen Saeed; Shah, Nasim Zahid; Shahid, Shahnaz; Zafar, Shehla Naeem
Abstract : Background/Aims: The high maternal mortality in Pakistan stems from pregnancy- or abortion-related complications. Pakistan's patriarchal society, where men are key decision-makers, makes it necessary to involve men in maternal and child reproductive health care initiatives. This study aimed to understand men's perceptions of post-abortion care in Karachi, Pakistan. Methods: A descriptive qualitative exploratory research design was used. Data were collected from 10 participants through in-depth interviews, and were analysed thematically. Results: The themes were 'men's understanding of post-abortion care', 'barriers to post-abortion care' and 'men's role in enhancing postabortion care practices: a missing link'. The participants believed that abortion was allowed only on medical grounds, and that most women could not use post-abortion care services because of the associated cost. Conclusions Men are key decision-makers in Pakistan. There is a need to educate and provide men with adequate information on post-abortion care. Male health workers should be recruited in the community. Stakeholders should ensure the availability and accessibility of post-abortion care services in the public health setting so women can receive care in a timely manner.